(untitled) (Ricos Biology, 2023)
Probiotics are beneficial microorganisms that improve the microbial balance of a host animal in all species. Immunomodulators are substances that keep tuning the immune system, so that probiotics are considered as immunomodulators that can stimulate the immune system of the host. Probiotics have many different bacterial species, Lactobacillus, Bifidobacterium, Bacillus and Enterococcus. They used to ameliorate certain physiological functions, safeguard of disease and mitigation of risk factors. Immunomodulation is a complex phenomenon that needs careful consideration, understanding of mechanisms of probiotic activities and immune functionality along either systematic or locally in GIT. Probiotics able to modulate the immune response via regulating the mediators secreted by intestinal immune system cells and T helper cell as well as regulatory cell stimulation. The interactions between probiotics and immune cells (enterocytes) are complex that is not achieved by a single mechanism. Probiotics are not immune specific, but they have been shown different mechanisms like production of mucin, reduction of permeability of GIT, increasing phagocytic capacity and activation of macrophage and natural killer (NK) cell. On the other hand, cytokines and other regulatory substances are increasing as well as antibodies production (IgA, IgM, and IgG). This review has discussed the probiotics immunological mechanisms in the farm animals.